Handbook of regional growth and development theories - Capello, Roberta, 1962-; Nijkamp, Peter, 1946- (Edward Elgar Publishing, 2019)
In recent years, economic crises, regional fragmentation trends, radical technological innovation and the failures of regional policies have expanded the knowledge horizon of experts in regional growth and development. This fully updated, revised and expanded second edition contains ten new chapters as well as exploring theories prevalent in the first edition in the face of recent changes in the field. With 30 chapters from leading experts from across the globe, this handbook looks at new pathways in regional economics, presenting the most cutting-edge theories explaining regional growth and local development. It thoroughly examines recent advances in theories, the normative potentialities that they have and the cross-fertilisation of ideas between regional and mainstream economists, providing crucial insights to the topic.